Increased expression of plakophilin 3 is associated with poor prognosis in ovarian cancer. Issue 10 (March 2019) - Qian, Hua; Yuan, Donglan; Bao, Jingjing; Liu, Fuxing; Zhang, Wenyan; Yang, Xumei; Han, Gaohua; Huang, Junxing; Sheng, Haihui; Yu, Hong
Abstract : Abstract: Considering the essential role of plakophilin 3 ( PKP3 ) in the maintenance cell-cell adhesion, dysregulation of PKP3 is involved in human diseases. This study aimed to explore the clinical significance of PKP3 in ovarian cancer. Immunohistochemistry was performed to examine the PKP3 expression in 157 cancer specimens from primary ovarian cancer patients. PKP3 was expressed in both the cytoplasm and nucleus. Eighty-one (51.6%) out of 157 ovarian cancer tissues showed PKP3 expression, while absent expression was observed in normal ovarian tissues. High PKP3 expression was associated with lymph node metastasis (LNM, P = .004) and advanced International Federation of Gynecology and Obstetrics (FIGO) stage ( P = .013). Patients with high PKP3 expression had shorter overall survival (OS) than those with low PKP3 expression (60.2 months vs 74.2 months, P = .021). However, no association between PKP3 expression and progression-free survival (PFS) was observed ( P = .790). Cox regression analysis indicated that PKP3 expression was an independently predictive factor for the OS of patient with ovarian cancer (adjusted HR = 1.601, 95%CI: 1.014-2.528, P = .043), especially those with FIGO stages III and IV disease (adjusted HR = 1.607, 95%CI: 1.006–2.567, P = .047). The gene expression profiling interactive analysis (GEPIA) databases also showed that PKP3 was upregulated in ovarian cancer ( P < .001) and patients with high PKP3 expression had shorter OS ( P = .004). In conclusion, our findings suggest that PKP3 is upregulated in ovarian cancer and is likely involved in the progression of ovarian cancer. PKP3 might therefore serve as a prognostic biomarker for patients with ovarian cancer. Abstract : Supplemental Digital Content is available in the text